The self versus institutions in J. D. Salinger’s The Catcher in the Rye and Franny and Zooey - Baroi, Windrila (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2017.